Arabica Coffee Price Prediction Using the Long Short Term Memory Network (LSTM) Algorithm - Setiyani, Lila; Utomo, Wiranto Herry (Universitas Negeri Semarang, 2023)
Purpose: Arabica coffee beans have been widely cultivated in various parts of the world. The need for coffee beans is estimated to increase every year. This was followed by the rapid growth of franchised coffee shops and cafes, therefore Arabica coffee beans have been traded legally in the world, thus making the price of these Arabica coffee beans a public concern. This prediction of the price of Arabica coffee beans can be input for business actors in the coffee shop, café franchises, and farmers in the decision-making process. This study aims to predict the price of Arabica coffee beans in 2023 and 2024 using the long short-term memory (LSTM) Algorithm.Methods: The research procedure is carried out by collecting data, data analysis, and preprocessing, and building a forecasting model using the Long Short-Term Memory Network (LSTM) algorithm. Arabica coffee bean price datasets in this study were taken from The Pink Sheet World Bank Commodity Price Data, which presents Arabica coffee bean prices from 1960 to February 2023.Results: The results of this study indicate the predicted price of Arabica coffee beans in 2023 and 2024 with Error (MAE), which is the average absolute difference between the actual value and the predicted value.Novelty: What is most important and what differentiates it from previous research is in the preprocessing using two algorithms namely MinMaxScaler and Sliding Window. Meanwhile, for the training model, GridSearchCV is used. The model is evaluated using the lost function using Mean Squared Error (MSE) and Mean Absolute Error (MAE) thereby making it easy to evaluate the performance of the model.